ChemInform Abstract: Synthesis of 3‐Aminochromenes: The Zincke Reaction Revisited. Issue 51 (23rd December 2014) - Costa, Marta; Rodrigues, Ana I.; Proenca, Fernanda
Abstract 3‐Aminocoumarins (II) and 2‐iminochromen‐3‐amines (IV) are prepared via Zincke‐ring‐opening reaction of corresponding chromen‐3‐pyridinium chlorides (I) and (III), resp., using N‐methylpiperazine.